Development And Characterization Of Edible Films From Sago Starch/Surimi By-Products Fish Gelatin Blends - Al-Hassan, Ahmed Ali S. (2011)
Physicochemical and thermal properties of extracted fish gelatin (EFG) obtained from surimi wastes were investigated and compared with those of fish gelatin (CFG) and halal bovine gelatin (HBG) from commercial preparations. Extracted fish gelatin was characterized for its physicochemical properties such as colour, amino acid composition, elemental content, structural analysis by FTIR and for its thermal properties. From differential scanning calorimetry (DSC) experiments, melting and gelling temperatures of EFG obtained were 16.2 ± 0.2 °C and 5.27 ± 0.4 °C, respectively and from rheological measurements, they were 16.7 ± 0.1 °C and 5.1 ± 0.1 °C, respectively. Both results obtained for EFG were much lower than that of CFG and HBG. Significantly lower viscosity of EFG was observed compared to other gelatins.